MULTI-PURPOSE AGRICULTURAL ROBOTIC VEHICLE - Dr Pavan Mankal; G Rakshita; Shradha Patil; Pragati Biradar; Ambika P G (International Educational Journal of Science and Engineering, 2026)
This project focuses on the development of a multipurpose agricultural robotic vehicle designed to automate essential farming tasks. The system is capable of performing operations such as seed sowing, irrigation, and pesticide spraying using a microcontroller and sensor-based setup. It can be controlled remotely or operate autonomously, ensuring accurate and efficient field operations. The robot reduces human effort, saves time, and improves resource utilization. Overall, it offers a cost-effective and practical solution to enhance productivity in modern agriculture. (Abstract)